2022
DOI: 10.2147/ijgm.s382631
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Hepatic and Renal Biochemical Tests for the Detection of Preeclampsia Among Pregnant Women Attending the Antenatal Care Clinic at the University of Gondar Comprehensive Specialized Hospital, Gondar, Northwest Ethiopia

Abstract: Background: Preeclampsia has a deleterious effect on renal and liver function, which results in alterations of various biochemical tests. Therefore, the main aim of this study was to evaluate the role of some hepatic and renal biochemical tests in the diagnosis of preeclampsia. Methods: A comparative cross-sectional study was carried out on a total of 126 pregnant women after 20th week of gestation who attended at the University of Gondar Comprehensive Specialized Hospital. The participants were divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…This is due to the fact that the reduction is only 15.15% as found in the present meta-analysis, and there are discrepancies in the literature regarding the extent of changes in activity expected in pregnancy with PE (reviewed in Table 2). It is possible that the determination of BChE activity during PE could be of value for assessment and follow-up, especially in the initial stages of monitoring and evaluation of the hypertension condition, when used collectively with other biomarkers such as liver enzymes, blood biochemical measurements, and oxidative stress markers [5][6][7][8][9][10][11]48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the fact that the reduction is only 15.15% as found in the present meta-analysis, and there are discrepancies in the literature regarding the extent of changes in activity expected in pregnancy with PE (reviewed in Table 2). It is possible that the determination of BChE activity during PE could be of value for assessment and follow-up, especially in the initial stages of monitoring and evaluation of the hypertension condition, when used collectively with other biomarkers such as liver enzymes, blood biochemical measurements, and oxidative stress markers [5][6][7][8][9][10][11]48].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by elevated maternal blood pressure (systolic > 140, diastolic > 90 mmHg) with > 0.3 g proteinuria in 24 h urine collection; in severe cases of PE the systolic and diastolic blood pressures may exceed 160 and 110 mmHg, respectively, with 24 h urine proteinuria of > 5 g, as well as disorders involving one or more of the major organ systems of the body [1,2]. In addition to these clinical findings, accumulated evidence from many studies has suggested that several biochemical changes could be considered biomarkers of PE [3][4][5]. These include but are not limited to elevation of activities of liver function enzymes [5], increased serum uric acid [6], hepcidin [7] and cytokine [8] levels, Vit D3 deficiency [9] or changes in blood cholinesterase (ChE) activity [10,11] and increased oxidative stress condition in the blood [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation